0

What equation is equivalent to 3[x + 3(4x – 5)] = 15x – 24?

Updated: 4/28/2022

Kaya Stokes

Lvl 1
3y ago

39x - 45 = 15x - 24

Kenyatta Baumbach

Lvl 10
3y ago

Earn +20 pts
Q: What equation is equivalent to 3[x + 3(4x – 5)] = 15x – 24?
Submit
Still have questions?
Related questions

Solve the equation 15x minus 12 equals 3x plus 8?

15x minus 8=minus 180 3x+8=24

When -34x-9 equals 24 is solved for x there is no solution true or false?

false, there is a solution -34x - 9 = 24 +9 +9 -34x = 33 x= - 33/34 or x = -.970588

15x - 8 - 3x equals 16?

Set up the equation and solve: 15x - 8 - 3x = 16 (next add 8 to each side) 15x - 3x - 16 + 8 (next simplify) 12x = 24 (next divide both side by 12 to solve for x) x = 2

If 15x equals 360 then x equals?

If: 15x = 360 then x equals 360/15 = 24

5x - 7y equals -40 3x equals 2y - 24?

Presumably this is a simultaneous equation question. 5x-7y = -40 3x = 2y-24 3(5x-7y = -40) 5(3x-2y = -24) After aligning the letters and numbers multiply the top equation by 3 and the bottom equation by 5. Note that 2y is now -2y because it has moved over to the other side of the equation. 15x-21y = -120 15x-10y = -120 To eliminate x subtract the bottom equation from the top equation remembering that a - - is equal to a + 0-11y = 0. So y will = 0 Substitute the value of y into the equations to find the value of x Solution: x = -8 and y = 0

15(x-3) :)

What is 7x plus 4(2x - 6) simplified?

It is 15x -24 when simplified

24

How do you factor x4 plus 4x3-7x-34x-24?

(x - 3)(x + 1)(x + 2)(x + 4)

The charge for a one-day rental of a car from shurtz car rental agency is 24 plus 15 cents for each mile driven if Jill drives 85 miles how much is the charge how many miles for 42?

f(x)=mx+b m= .15 (slope) b=constant f(x)=.15x+ 24 f(85)=.15(85)+24= \$36.75 -------------------------------------------------- f(x)=.15x+24=\$42 -24 -24 f(x)=.15x=\$42 .15/42 x=120mi

Caleb and Roberto also solved the equation but they made some errors. Find an incorrect step in each solution and explain why it is incorrect.Caleb12x+3 = 3(5x+9)7x+3=3(9)7x+3=277x=24x=24/7Roberto12x+3=3(5x+9)12x+3=15x+2727x+3=2727x=24x=24/27?

Caleb's solution: 12x + 3 = 3(5x + 9) 7x + 3 = 3(9) (incorrect step) 7x + 3 = 27 (correct next step if previous step were correct) 7x = 24 x = 24/7 Caleb's incorrect step is going from the first line to the second line. The distribution of the 3 on the right-hand side of the equation should result in 15x + 27, not 3(9) which is 27. So the correct next line should be: 12x + 3 = 3(5x + 9) 15x + 27 = 15x + 27 (distribute 3 on the right-hand side) 12x + 3 = 15x + 27 (subtract 15x from both sides) -3x = 24 x = -8 Roberto's solution: 12x + 3 = 3(5x + 9) 12x + 3 = 15x + 27 (incorrect step) 27x + 3 = 27 (correct next step if previous step were correct) 27x = 24 x = 24/27 Roberto's incorrect step is going from the first line to the second line. Adding 3 to both sides of the equation does not result in the distribution of 3 on the right-hand side. The correct next line should be: 12x + 3 = 3(5x + 9) 12x + 3 = 15x + 27 (distribute 3 on the right-hand side) -3x = 24 x = -8/3 or approximately -2.67 Therefore, Caleb's solution has the correct final answer, but an incorrect step, while Roberto's solution has both an incorrect step and an incorrect final answer.

How do you do an equivalent equation 38 equals a plus 12?

38=a + 12. A is not divisible evenly, so to get another equivalent equation you can multiply everything by the same thing, i.e. 2 being easiest. 76=2a + 24